Tumoricidal effect of skeletal vibratory signal during Al-Fatihah recitation on human cancer cells - Abdullah, Abu Dzarr Ganesh (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
This research attempts to study if physical vibration generated in the human body during recitation of AIFatihah has an effect on cancer cells. This includes working sequentially on two main objectives. The first objective is to measure and model skin vibration signals using accelerometer (skin acceleration level) on a cohort of verified reciters whereby measurement is carried out during recitation. Subsequently the modeled vibration is simulated on cancer cells (NCI H929: Myeloma) and its growth and viability assessed. At the time of this final report the first objective was not achieved hence prevented progression to the second objective. A cohort of 15 reciters has been established but we could not proceed to gauge skin acceleration level as currently available methods were found to be unreliable. Current methods of mounting accelerometer to the skin produce highly variable acceleration amplitudes. Various alternatives were devised and attempted, such as using polystyrene, plastic holders etc failed to fulfil gage repeatability and reproducibility criteria. Towards the end, preliminary gage study using suction cups as accelerometer mounting adapter showed promise but the final measurement analysis is yet to be carried out. This research is still ongoing in spite of the end of study period.